2020
DOI: 10.1021/acsami.0c11016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electric Potential and Chain Length on Tribological Performances of Ionic Liquids as Additives for Aqueous Systems and Molecular Dynamics Simulations

Abstract: As pure lubricants, ILs performed very well by forming the classical self-assembly bilayer at the sliding interface. The interface mechanism is still not clear in a very polar, e.g., water-based lubricating system. In this work, the interfacial absorption and tribological behavior of carboxylic alkanolamine ionic liquids (CAILs) serving as aqueous lubricating additives were studied by applying positive and negative potentials on the friction pair, accompanied by the comprehensive discussion of data from critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…Based on the reports in the literature, many commonly used CQDs in tribology are covalently modified by various ionic liquids and their derivatives, resulting in the outermost layer of these CQDs usually capped by negatively charged anions; then, CQDs in lubricating oils can be easily adsorbed onto the rubbing surfaces by electrostatic interaction to form a stable adsorption film. Consequently, the adsorption film could effectively prevent the rubbing surfaces from the direct contact, thereby significantly reducing the friction and wear of the friction pairs [168][169][170][171]. Other types of CQDs which were modified by nonionic liquid groups and oxygen-containing groups can also form an adsorption film on the rubbing surface by Van der Waals force.…”
Section: Physical Lubrication Filmmentioning
confidence: 99%
“…Based on the reports in the literature, many commonly used CQDs in tribology are covalently modified by various ionic liquids and their derivatives, resulting in the outermost layer of these CQDs usually capped by negatively charged anions; then, CQDs in lubricating oils can be easily adsorbed onto the rubbing surfaces by electrostatic interaction to form a stable adsorption film. Consequently, the adsorption film could effectively prevent the rubbing surfaces from the direct contact, thereby significantly reducing the friction and wear of the friction pairs [168][169][170][171]. Other types of CQDs which were modified by nonionic liquid groups and oxygen-containing groups can also form an adsorption film on the rubbing surface by Van der Waals force.…”
Section: Physical Lubrication Filmmentioning
confidence: 99%
“…Previous studies have shown that applying external electric fields can modify the molecular structure and charge transfer at solid-solid interfaces, thereby decreasing the interfacial friction and resistance [1,2]. Moreover, the distribution or orientation of ions at solid-liquid interfaces can be controlled and changed via electric fields to achieve the desired lubricating effect [3][4][5][6][7]. Electric-field-mediated lubrication is an attractive and promising route for improving tribological performance.…”
Section: Introductionmentioning
confidence: 99%
“…29 Diprotic ammonium palmitate ionic liquid crystal as an additive to water formed a lubricating thin film and reduced the coefficient of friction and wear rates of steel substrates. 29 Phosphate ester based protic ionic liquids as additive to water formed a doublelayer structure over the steel tribo interfaces via self-assembly process, which gradually led to tribochemical reaction and yielded the protective boundary thin film for reduction of friction and wear. 30 Ionic liquids have not been explored to a significant extent for aqueous lubricants, although they have great potential to extend lubrication properties.…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of protective tribo thin film was governed by the alkyl chain length of carboxylate anion. The physical adsorption of carboxylate anion and tribochemical reaction under the contact stress furnished a lubricious thin film of ionic liquid for aqueous lubrication . Diprotic ammonium palmitate ionic liquid crystal as an additive to water formed a lubricating thin film and reduced the coefficient of friction and wear rates of steel substrates .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation